WAYANG - Hatta Azad Khan; Zul Huzaimy; Mas Muharni; Eman Manan (Kuala Lumpur : Golden Satellite Marketing, 2008)
Story about Awang (Eman Manan), a Malaysian shadow puppeteer who, after his own child rejects him, warily adopts two children, one a blind orphan boy, to be taught as puppeteers. Conflict arises with relatives who think that Islam forbids wayang performances.--Summary adapted from container.
Title from container
U - This category is for viewing all levels of society without age limits. The film features pure values, courtesy and positive and entertaining teaching
DVD, MPEG 2, Surround 5.1, Malay Version, Approximately : 110 mins
In Malay version with English subtitles
Keywords: Motion picture films -- Malaysia; Shadow puppets -- Malaysia; Feature films